Socio-Cultural Features of Stimulating Scientific and Design Activities in Uzbekistan - Islambaev Ravshan Islambay O’g’li (Zien Journals, 2023)
The article discusses the socio-cultural aspects of stimulating the work of scientific and design activities. The definition of design activity is also given. The main features of stimulating the work of researchers are described, as well as recommendations for improving the effectiveness of incentives in research and development activities are given.
Keywords: Design activity; scientific and design activities; scientific and design education; motivation